MENGEMBANGKAN KEMAMPUAN MAHASISWA PENDIDIKAN BIOLOGI DALAM MENGISOLASI PLASMID BAKTERI SEBAGAI PENGAYAAN PRAKTIKUM MIKROBIOLOGI - Kusnadi, Kusnadi; Rochintaniawati, Diana; Kusumawaty, Diah (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2005)
This learning cycle focused on developing of Biology education student’s performance in bacteria DNA-plasmid isolation as well as using gel electrophroresis. The aim of the study was to improve student’s performance in operating equipment used in plasmid isolation such as: micropipettes, microsentrifuge, vortex, shaker-incubator, gel electrophoresis, and UV Trans-illuminator camera. Beside that students were also trained to DNA-plasmid isolation base on standard procedure, so students could identify the form of plasmid via the use of gel electrophoresis. This study was conducted in 2 cycle learning processes as an enrichment of microbiology activity, which associated with molecular microbes genetics. Using observation sheet did evaluation. The study revealed that biology education students had good performance in isolating the plasmid and all group were succeed to isolate the plasmid. Beside that there were increased in knowledge ability especially associated with molecular microbes genetics subject, which achievment gain average was 18,3% (Class A) and 35,4% (class B). The DNA isolation activity in microbiology learning shared high contribution as well as increasing of knowledge achievment and performance ability.